Response surface split‐plot designs: A literature review. (23rd July 2018) - Cortes, Luis A.; Simpson, James R.; Parker, Peter A.
Abstract: The fundamental principles of experiment design are factorization, replication, randomization, and local control of error. In many industrial experiments, however, departure from these principles is commonplace. Often in our experiments, complete randomization is not feasible because factor level settings are hard, impractical, or inconvenient to change, or the resources available to execute under homogeneous conditions are limited. These restrictions in randomization result in split‐plot experiments. Also, we are often interested in fitting second‐order models, which lead to second‐order split‐plot experiments. Although response surface methodology has experienced a phenomenal growth since its inception, second‐order split‐plot design has received only modest attention relative to other topics during the same period. Many graduate textbooks either ignore or only provide a relatively basic treatise of this subject. The peer‐reviewed literature on second‐order split‐plot designs, especially with blocking, is scarce, limited in examples, and often provides limited or too general guidelines. This deficit of information leaves practitioners ill‐prepared to face the many challenges associated with these types of designs. This article seeks to provide an overview of recent literature on response surface split‐plot designs to help practitioners in dealing with these types of designs.